Collective Mobilisations in Africa. Enough is Enough ! Mobilisations collectives en Afrique. Ça suffit ! - (:unkn) unknown (My University, 2015)
This book uses empirical research to bring together a broad range of protest contexts in twelve chapters. From the formation of Maroon societies in the early colonial period, to female mobilisation in authoritarian contexts, via urban youth culture, women or mineworkers in trade unionism, as well as pro- and anti- gay rights activists, the protagonists here all insist upon their rights to protest in a variety of ways. Sometimes popular protest is expressed through religion, often (and sometimes violently) by young people, exasperated by their long wait for social achievement. Electoral wars and the formation of militias reveal a geography of violence in urban areas, which, in some sectarian excesses, can be displaced to rural areas, as described in the study on Boko Haram. Contributors are: Rémy Bazenguissa-Ganga, Raphaël Botiveau, Christophe Broqua, Michel Cahen,Thomas Fouquet, Adam Hizagi, Alcinda Honwana, Alexander Keese, Marie-Nathalie LeBlanc, Dominique Malaquais, Marie-Emmanuelle Pommerolle, Ophélie Rillon, Johanna Siméant, Benjamin Soares, Kadya Tall.
Keywords: African Research